1999
DOI: 10.1016/s0006-3495(99)77138-9
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Octyl Ester in Detergent Micelles of Dodecylmaltoside: Fluorescence Properties and Quenching by Brominated Detergent Analogs

Abstract: The fluorescence properties of tryptophan octyl ester (TOE), a hydrophobic model of Trp in proteins, were investigated in various mixed micelles of dodecylmaltoside (DM) and 7,8-dibromododecyl beta-maltoside (BrDM) or 10,11-dibromoundecanoyl beta-maltoside (BrUM). This study focuses on the mechanism via which these brominated detergents quench the fluorescence of TOE in a micellar system. The experiments were performed at a pH at which TOE is uncharged and almost completely bound to detergent micelles. TOE bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 60 publications
(92 reference statements)
4
29
0
Order By: Relevance
“…However, it is being increasingly recognized that the hydrophobic fluorophore tryptophan octyl ester (TOE, structure shown in Fig. 1 inset) is a more suitable model for tryptophan, in case of membrane proteins (12)(13)(14)(15)(16)(17). Thus it is of considerable importance to carry out detailed characterization of the fluorescence emission properties of TOE in appropriate environments relevant to biomembranes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is being increasingly recognized that the hydrophobic fluorophore tryptophan octyl ester (TOE, structure shown in Fig. 1 inset) is a more suitable model for tryptophan, in case of membrane proteins (12)(13)(14)(15)(16)(17). Thus it is of considerable importance to carry out detailed characterization of the fluorescence emission properties of TOE in appropriate environments relevant to biomembranes.…”
mentioning
confidence: 99%
“…In particular, they investigated its partitioning and motional characteristics in such membranes as a function of its ionization state. More recently, Foresta et al (12) investigated the fluorescence properties of TOE in various mixed micellar systems of dodecylmaltoside (DM) and 7,8-dibromododecyl ␤-maltoside (BrDM) or 10,11-dibromoundecanoyl ␤-maltoside (BrUM). They found that the indole moiety of TOE is highly accessible to the bromine atoms located on the detergent alkyl chain because quenching by bromine occurs by direct contact with the fluorophore.…”
mentioning
confidence: 99%
“…84 This is a common observation made using this technique 9,13,26,45,85,86 as well as in MD simulations. 75,87−89 This slow relaxation has been proposed to be due to the motion of interfacial water in exchange with the bulk, 9,84 to the local dynamics of polar moieties belonging to the macromolecules or their assemblies, 90 or to the mobility of the probes themselves.…”
Section: ■ Discussionmentioning
confidence: 65%
“…[133][134][135][136][137][138][139] Tryptophan octyl ester (TOE) has been recognized as an important model for membrane-bound tryptophan residues. 62,[140][141][142] The fluorescence characteristics of TOE incorporated into model membranes and membrane-mimetic systems have been shown to be similar to that of membrane-bound tryptophans. Consistent with the preferred interfacial location of the tryptophan residue and the solvent-restricted environment of the interface, TOE has been found to exhibit REES.…”
Section: Monitoring Protein Structure and Dynamics By Rees 209mentioning
confidence: 98%